2005
DOI: 10.1007/bf03015774
|View full text |Cite
|
Sign up to set email alerts
|

Rapport sommaire: l’incidence décroissante de l’hyperthermie cérébrale pendant la cardiochirurgie, sept ans d’expérience auprès de 6 334 patients

Abstract: P Pu ur rp po os se e: : Cerebral hyperthermia during rewarming from hypothermic cardiopulmonary bypass (CPB) commonly occurs and has been associated with postoperative neurocognitive dysfunction. Increased awareness of this has likely led to changes in rewarming strategies, including the reduction of rewarming rates and lowering of target rewarming temperatures. As a result, we hypothesized that the maximum temperature reached during cardiac surgery has decreased at our institution over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
(17 reference statements)
0
0
0
Order By: Relevance
“…Not only is there evidence for progressive uptake of some of the relevant recommendations (27), there is also evidence (albeit somewhat circumstantial) that progress on risk reduction has been achieved over the period of interest. For example, we used similar measurement methodology and definitions of POCD in two separate neuroprotection studies almost 10 years apart in the same cardiac surgical suite (28,29) and found that the incidence of early deficits in the control group fell from 75% to 41%.…”
Section: Historical Perspectivementioning
confidence: 99%
“…Not only is there evidence for progressive uptake of some of the relevant recommendations (27), there is also evidence (albeit somewhat circumstantial) that progress on risk reduction has been achieved over the period of interest. For example, we used similar measurement methodology and definitions of POCD in two separate neuroprotection studies almost 10 years apart in the same cardiac surgical suite (28,29) and found that the incidence of early deficits in the control group fell from 75% to 41%.…”
Section: Historical Perspectivementioning
confidence: 99%